Is dark energy – an alias of cosmic rotational kinetic energy? - UV, Satya Seshavatharam; S, Lakshminarayana (International Journal of Advanced Astronomy, 2016)
Considering Planck scale and Mach’s principle, theoretically it is possible to show that magnitude of the currently believed dark energy is equal to the magnitude of current cosmic rotational kinetic energy.